High-flow oxygen therapy in elderly patients infected with SARS-CoV2 with a contraindication for transfer to an intensive care unit: A preliminary report - Jean-Christophe Lagier; Sophie Amrane; Morgane Mailhe; Marc Gainnier; Sylvie Arlotto; Stéphanie Gentile; Didier Raoult (International Journal of Infectious Diseases, 2021)
Objectives: In a conventional hospital ward, we used high-flow nasal oxygen (HFNO) to treat elderly COVID-19 patients noneligible for intensive care unit transfer. Methods: This study was conducted in the Institut Hospitalo-Universitaire Méditerranée Infection, Assistance Publique-Hôpitaux de Marseille (AP-HM), France. We used high-flow nasal oxygen (HFNO) in our conventional infectious disease ward from 15 September 2020 for elderly patients noneligible for intensive care unit transfer. Results: Of the 44 patients (median age 83 years (57–94), mean: 80.25), 61.4% (27/44) were men. The median Charlson score was 7 (1–15). The median of the NEWS-2 score upon admission was 8 (3–11) and was 10 at the time of initiation of HFNO. The median PaO2/FiO2 ratio was 103 (71–151) prior to HNFO initiation. Among the 44 patients, 16 patients (36.4%) had been weaned from HFNO, and 28 patients had died (63.6%). Conclusions: In this preliminary report, we observed that HFNO saved the lives of one-third of elderly COVID-19 patients who would have systematically died.